The Effect of Training and Motivation on Employee Performance - Handayani, Rima (PINISI Discretion Review, 2018)
The biggest real threat to economic stability is a workforce that is not ready to face the challenges or changes around it. The purpose of this study was to determine the effect of training and motivation on the performance of employees of PT. Sentra Jaya Distribution Tangerang. The research method uses quantitative with a population of 120, determining the sample using the Slovin formula with an error rate of 10% obtained 54 respondents. Data collection methods using primary data and secondary data. Test the instrument using the validity and reliability test, the prerequisite data test uses the normality test, the autocorrelation test, the multi-collinearity test, and the heteroscedasticity test, while the statistical tests use the multiple regression equation, the correlation coefficient test, the coefficient of determination test and the significance test. The Effect of Training and Motivation on Employee Performance at PT. Distribution of Sentra Jaya Tangerang, the analysis of the data that the researchers concluded that the regression equation Y = a + b1X1 + b2X2 which was found was Y = 15.454 + 0.387 X1 + 0.265 X2, with the multiple correlation coefficient R was 0.563, this showed a positive effect. Then get the equation Tcount> T table (2.478> 2.008) in the hypothesis test at Î± = 0.05 or 5% (significance 0.003 <0.05) then, thereby indicating the hypothesis proposed is accepted, or in other words, Ho is rejected and Ha is accepted. Thus there is a positive and significant effect between the provision of training and motivation on the performance of employees of PT. Sentra Jaya Distribution Tangerang